In Vivo ZIMIR Imaging of Mouse Pancreatic Islet Cells Shows Oscillatory Insulin Secretion - Chen, Shiuhwei; Huang, ZhiJiang; Kidd, Harrison; Kim, Min; Suh, Eul Hyun; Xie, Shangkui; Ghazvini Zadeh, Ebrahim H.; Xu, Yan; Sherry, A. Dean; Scherer, Philipp E.; Li, Wen-hong (Frontiers in Endocrinology, 2021)
Appropriate insulin secretion is essential for maintaining euglycemia, and impairment or loss of insulin release represents a causal event leading to diabetes. There have been extensive efforts of studying insulin secretion and its regulation using a variety of biological preparations, yet it remains challenging to monitor the dynamics of insulin secretion at the cellular level in the intact pancreas of living animals, where islet cells are supplied with physiological blood circulation and oxygenation, nerve innervation, and tissue support of surrounding exocrine cells. Herein we presented our pilot efforts of ZIMIR imaging in pancreatic islet cells in a living mouse. The imaging tracked insulin/Zn2+ release of individual islet beta cells in the intact pancreas with high spatiotemporal resolution, revealing a rhythmic secretion activity that appeared to be synchronized among islet beta cells. To facilitate probe delivery to islet cells, we also developed a chemogenetic approach by expressing the HaloTag protein on the cell surface. Finally, we demonstrated the application of a fluorescent granule zinc indicator, ZIGIR, as a selective and efficient islet cell marker in living animals through systemic delivery. We expect future optimization and integration of these approaches would enable longitudinal tracking of beta cell mass and function in vivo by optical imaging.